Implementation of Constructivist Learning Theory in Differentiated Learning Strategies in the Merdeka Curriculum for 5th Grade MI Al-Ma`had Roudlotul Huda - Firda Zakiyatur Rofi’ah; Siti Farichatul Ula; Azizah Nur Avivah (Journal of Practice Learning and Educational Development, 2025)
Constructivism theory is an approach aligned with the Merdeka Curriculum that positions students as active subjects in constructing knowledge through meaningful learning experiences. This research aims to describe the implementation of constructivism learning theory in differentiated learning strategies in Class V MI Al-Ma`had Roudlotul Huda. This research uses a qualitative descriptive method, with data collection techniques through observation of learning activities, interviews with class teachers, and documentation of lesson plans. The implementation of constructivist theory in differentiated learning strategies within the Merdeka Curriculum for 5th grade at MI Al Ma'had Roudlotul Huda shows positive results, especially in accommodating kinesthetic learning styles. Learning is designed so that students do not just passively receive material, but actively build understanding through direct activities such as projects, experiments, simulations, and environmental observation. Students with kinesthetic learning styles are given space to explore learning material physically and concretely, making learning more meaningful and aligned with their learning characteristics. Teachers act as facilitators who design a learning environment rich in experience, support collaboration, and encourage students to reflect on the knowledge they construct themselves. Thus, the application of constructivism learning theory in differentiated learning strategies is proven to support the achievement of the Merdeka Curriculum's goals, especially in shaping students who are independent in learning and developing according to their potential.